Structural and Optical Properties of Electro Sprayed Tin Oxide Thin Films - K.P. Devasenathipathi; V. Arivazhagan; M. Manonmani Parvathi; S. Rajesh (Журнал нано- та електронної фізики)
Semiconducting transparent SnO2 thin films were prepared by microcontroller processed electro spraying technique. The structural and optical properties of the films were studied using X-ray diffractometer, UV-Vis spectrophotometer and Photoluminescence spectroscopy respectively. The polycrystalline nature of the films with tetragonal structure was observed from XRD pattern with the mean grain size of 17 nm. The Optical band gap of the films was calculated from the absorption curve and the interference pattern was observed on transmittance spectra. The calculated band gap of 3.5 eV is larger than the bulk band gap of Tin oxide. The blue emission band at 388 nm was observed from room temperature photoluminescence analysis and the effect of excitation wavelength of the films were studied and discussed.